Reinstatement of Pedicularis delavayi (Orobanchaceae): a species separating from P. siphonantha revealed by phylogenetic analyses - Yu,Wen-Bin; Wang,Hong; Liu,Min-Lu; Grabovskaya,Alisa E.; Li,De-Zhu (PeerJ Preprints, 2016)
Background. Morphological identification of Pedicularis depends on floral characters because interspecific variations these characters is very large. However, some important characters may be lost during the process of pressing the specimen. Pedicularis delavayi was described from Lijiang, northwestern Yunnan, and it was widely adopted as a variety of P. siphonantha. Unfortunately, the name “P. siphonantha var. delavayi’ incorrectly referred to P. milliana/P. tenuituba in some identified specimens and publications. Moreover, phylogenetic relationships between P. delavayi and P. siphonantha and its allies (P. millana and P. tenuituba) were not fully resolved. Methods. In total, we sampled 75 individuals representing 56 taxa. Of them, 10 taxa were from P. siphonantha group, and 11 individuals of P. delavayi represented 9 populations. One nuclear gene (nrITS) and four chloroplast genes/regions (matK, rbcL, trnH-psbA, and trnL-F) were sequenced for phylogenetic analyses. The nrITS and plastid datasets were combined to analyze. Bayesian Inference (BI) and Maximum Likelihood (ML) methods were used to reconstruct phylogenetic trees. Species identification, morphological comparison and line drawing were based on field observation, dried herbarium specimens and FFA-fixed samples. Results. Phylogenetic analyses showed that the P. siphonantha group was polyphyletic: monophyletic P. delavayi, sister to P. obliquigaleata, fell into clade A; and the remaining species of P. siphonantha group was in clade B as monophyletic (i.e. P. siphonantha lineage). In the P. siphonantha lineage, P. milliana, P. siphonantha, and P. tenuituba (= P. siphonantha var. stictochila) were well supported as monophyletic, and P. dolichosiphon (≡ P. siphonantha var. dolichosiphon) was sister to P. leptosiphon. Morphologically, P. delavayi differs from species of the P. siphonantha lineage in having a long petiole (~ 50 mm) and pedicel (~ 40 mm), a ridged corolla tube, and a folded lower-lip of the corolla. Discussion. Phylogenetic analyses showed evolution of P. delavayi was independent from the P. siphonantha lineage. The long-tubular corollas in P. delavayi and P. siphonantha lineage might be a convergent character. Both morphological and phylogenetic evidence strongly supported to reinstate P. delavayi as an independent species. In addition, P. neolatituba was proposed to reduce as a new synonymy of P. delavayi.
Keywords: Pedicularis delavayi; Pedicularis milliana; species delimitation; Pedicularis; the Hengduan Mountains; Pedicularis siphonantha